The Effect of Adaptive Ability, Communication Skills, and Work Environment on Performance of Medan Mayor's Office with Teamwork as Intervening Variables - Siti Novia Rachmawati; Prihatin Lumbanraja; Elisabet Siahaan (Journal Research of Social Science, Economics, and Management, 2021)
Having a reasonable effort of adapting to the change will improve the organization's performance. Good communication with the leaders, colleagues, and employees will ease communicating the organization's problems for achieving the best organizational performance. A good work environment will influence more the employee's motivation to work to improve the employee's performance. Conducting the working programs, the government will establish teamwork to fasten the organization's performance achievement. This research aims to analyze the influence of adaptability, communication skills, and working environment on employee performance at Medan Mayor's Office with teamwork as the intervening variable. This research population is government employees at Medan mayor's office with a total of 555 employees, with the amount of the sample being 232 employees. The analysis uses statistics and path analysis. The result shows the adapting ability, communication skills, and working environment directly significantly influence teamwork, and then the adaptability, communication skill, and work environment positively and significantly affect employee performance. Indirectly, collaboration is positively and significantly able to mediate the relationship between adaptability, communication skill, work environment, and employee performance. Therefore, teamwork is significantly able to be the intervening variable in this research.